Per- and polyfluoroalkyl substances in rainfall runoff from an AFFF-impacted concrete pad: A field simulation study - Phong K. Thai; Jeffrey T. McDonough; Trent A. Key; Anita Thapalia; Scott Porman; Pritesh Prasad; Stephanie Fiorenza; Hirozumi Watanabe; Craig M. Barnes; Jochen F. Mueller (Journal of Hazardous Materials Letters)
Per- and polyfluoroalkyl substances (PFAS) retained within hardscape have been observed to leach over time in numerous laboratory studies. The aim of this study was to measure the release of key PFAS in rainfall runoff from a concrete pad impacted by historical AFFF use at the field-scale. Rainfall simulations were conducted on a 5 m2 (1 ×5 m) plot for 3 consecutive days. Runoff water was collected every 2 minutes and analyzed for 5 PFAS commonly associated with AFFF. Surface samples of the concrete were collected from the plot after the rainfall runoff experiment. Perfluorooctane sulfonate (PFOS) exhibited the highest concentrations within the concrete (up to ∼4000 μg kg−1) and runoff water (up to 500 μg L−1), followed by 6:2 fluorotelomer sulfonate (6:2 FTS). PFAS concentrations in runoff water were higher in the first sample and then decreased in the consecutive samples of each rainfall simulation. It is estimated that the percentage of the total PFAS mass within the surface of the concrete contributing to runoff samples ranged from 0.006 % (PFOS) to 0.031 % (PFHxA) per rainfall event. This suggests low but sustained PFAS leaching from AFFF-impacted concrete into runoff water. Our findings confirmed that concrete impacted by legacy use of AFFF is a likely secondary source of PFAS in runoff water and highlight some similarities and differences between laboratory- and field-scale rainfall simulations.